Perencanaan Edu-Ekowisata Berbasis Atraksi Wisata di Kebun Percobaan dan Penelitian Jonggol, Institut Pertanian Bogor (IPB) University - Hikmah, Ziyadatul; Muntasib, E.K.S. Harini; Kosmaryandi, Nandi (Jurnal Ilmu Kehutanan, 2025)
The Jonggol Teaching and Research Farm serves as a field laboratory for Institut Pertanian Bogor (IPB) University, featuring a diverse array of agricultural and livestock systems, including plantations of oil palm, cassava, sorghum, and indigofera, as well as sheep and cattle farming, alongside agricultural and livestock processing industries. The research aimed to develop an edu-ecotourism plan that leverages existing tourist attractions. The planning process involved preparation, data collection through field surveys, resource inventory, and interviews with managers. Employing both descriptive and spatial analyses, the research synthesized concepts and site planning. The data analysis encompassed physical, biophysical, tourism, and management aspects. Findings revealed that edu-ecotourism plays a vital role in tourism planning, functioning as an educational resource for environmental character development and a means to showcase agricultural innovations. The research identified ten tourist attractions at the Jonggol Teaching and Research Farm, which include the Sorinfer factory, various plantations, field laboratories, guest houses, and natural resources (31 flora, 2 cultivated animals, and 20 wildlife species), as well as notable topographical, geological, and soil variations, complemented by visual beauty. The resulting edu-ecotourism plan encompassed designated tourist spaces, circulation plans, green planning zones, and activity plans that incorporate interpretation services, such as attraction maps.